Kawasaki disease in infants less than one year of age: an Italian cohort from a single center - Greta Mastrangelo; Rolando Cimaz; Giovani Battista Calabri; Gabriele Simonini; Donatella Lasagni; Massimo Resti; Sandra Trapani (BMC, 2019)
Abstract Background and aims Few data are currently available for Kawasaki disease (KD) below 12 months especially in Caucasians. This study aims to analyze clinical and laboratory features of KD among an Italian cohort of infants. Methods A retrospective chart review of KD children aged less than 1 year at time of disease onset between January 2008-December 2017 was performed. Clinical data, laboratory parameters, instrumental findings, treatment and outcome were collected in a customized database. Results Among 113 KD patients, 32 (28.3%) were younger than 1 year. Nineteen patients aged below 6 months, and three below 3 months. The median age was 5.7 ± 2.7 months. The mean time to diagnosis was 7 ± 3 days and was longer in the incomplete forms (8 ± 4 vs 6 ± 1 days). Conjunctival injection was present in 26 patients (81.2%); rash in 25 (78.1%); extremity changes in 18 (56.2%); mucosal changes in 13 (40.6%,) and lymphadenopathy only in 7 (21.8%). Mucosal changes were the least common features in incomplete forms (18.2%). Twenty-two patients (68.7%) had incomplete KD. Nineteen (59.4%) had cardiac involvement, of whom 13 (59.0%) had incomplete form. ESR, PCR and platelet values were higher in complete KD; especially, ESR resulted significantly higher in complete forms (80 ± 25.7 mm/h vs 50 ± 28.6 mm/h; p = 0.01). Conversely, AST level was statistically significant higher in patients with incomplete forms (95.4 ± 132.7 UI/L vs 29.8 ± 13.2 UI/L; p = 0.03). All patients received IVIG. Response was reported in 26/32 patients; 6 cases needed a second dose of IVIG and one required a dose of anakinra. Conclusion In our cohort, incomplete disease was commonly found, resulting in delayed diagnoses and poor cardiac prognosis. Infants with incomplete KD seem to have a more severe disease and a greater predilection for coronary involvement than those with complete KD. AST was significantly higher in incomplete forms, thus AST levels might be a new finding in incomplete forms' diagnosis. Eventually, we highlight a higher resistance to IVIG treatment. To our knowledge this is the first study involving an Italian cohort of patients with KD below 12 months.